Six Sigma Infrastruc​ture for Cataract Surgery in Patients with Pseudoexfo​liation Syndrome - Sahbaz, Ibrahim; Taner, Mehmet Tolga; Kagan, Gamze; Durmus, Ebubekir; Tunca, Meltem; Erbas, Engin; Kagan, Sabahat Beyza; Kagan, Mehmet Kemal; Enginyurt, Hazar (Archives of Business Research, 2014)
The goal of this study is to show how an eye clinic of a Turkish public hospital initiated Six Sigma principles to reduce the number of complications encountered during and after cataract surgeries in patients with pseudoexfoliation (PEX) syndrome. : Data were collected for three years. To analyse the process, main tools of Six Sigma’s Define-Measure-Analyze-Improve-Control (DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Sources and root causes of ten types of complications were identified and reported. Experience of the refractive surgeon, patient’s anatomy, cooperation of patient during the surgery, sterilization and hygiene, attention of assistant surgeon, calibration of equipment and quality/chemical composition of intraocular material were identified to be Critical-to-Quality (CTQ) factors for a successful surgery. The most frequently occurring complication was found to be posterior capsule rupture. The overall process sigma level for 3 years was measured to be 3.703. The surgical team concluded that all complications should be significantly reduced by taking the necessary preventative measures.